Elements of Cosmological Thermodynamics - Saha, Subhajit (SpringerBriefs in Physics,, 2018)
Based on the author's own work and results obtained by renowned cosmologists, this short book provides a concise introduction to the relatively new research field of cosmological thermodynamics. Starting with a brief overview of basic cosmology and thermodynamics, the text gives an interesting account of the application of horizon thermodynamics to the homogeneous and isotropic Friedmann-Lemaitre-Robertson-Walker (FLRW) model, the inhomogeneous (Lemaitre-Tolman-Bondi) LTB model, and the gravitationally induced adiabatic particle creation scenario which is considered to be a viable alternative to the concordance Lambda-CDM model of the Universe. Both seasoned and new researchers in this field will appreciate the lucid presentation and the rich bibliography.